PENGARUH ACID TEST RATIO, DEBT TO ASSETS RATIO, DAN GROSS PROFIT MARGIN TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2017 - Gabriel Delfero Samosir; Pebrina Megawati Pangaribuan; Sri Wira Hayati Habeahan; Samuel Abel Tanta Sembiring; Jholant Bring Luck Amelia (Jurnal Akrab Juara, 2019)
This study aims to determine Acid Test Ratio, Debt to Assets Ratio and Gross Profit Margin to Financial Performance in various industrial sector companies. This research method uses a purposive sampling method with a sample of 44 various industrial sector companies listed on the Indonesia Stock Exchange for the period 2014-2017. The analytical method used is the method of multiple linear regression analysis. The results of the coefficient of determination Effect of Acid Test Ratio, Debt to Assets Ratio and Gross Profit Margin on Financial Performance amounted to 0.128. This shows that 12.8% variation of acid test ratio, debt to assets ratio and gross profit margin can explain the relationship to financial performance, while the remaining 87.2% is explained by other variables. The results of this study indicate that partially Acid Test Ratio Gross dan Debt to Assets Ratio and Gross Profit Margin have not a significant effect on financial performance while Gross Profit Margin significant effect on financial performance. Simultaneously Acid Test Ratio, Debt to Assets Ratio and Gross Profit Margin significantly influence the financial performance of various industry sectors.